EXAMINING THE CRIMINAL RESPONSIBILITY OF THE INDONESIAN FOOD AND DRUG AUTHORITY REGARDING THE DISTRIBUTION LICENSE OF SYRUP MEDICINES IN CASES OF ACUTE KIDNEY FAILURE - Putri Nabila Sahwahita; Eliska Vioni; Salma Agustina (Journal Social Sciences and Humanioran Review, 2024)
In 2022, there was a phenomenon of cases of Atypical Progressive Acute Kidney Disorders in Children. After laboratory examinations were carried out by The Indonesian Food and Drug Authority together with other institutions, it was found that the compounds Ethylene Glycol (EG), Diethylene Glycol (DEG), and Ethylene Glycol Butyl Ether (EGBE) exceeded the limits in syrup medicines consumed by children. Based on this, this research aims to determine criminal responsibility by BPOM as the party that supervises all distribution of medicines and food regarding the distribution of syrup medicines which cause acute kidney failure in children and indications of the application of the murder article in the Criminal Code as BPOM's responsibility. The object of study in regulating legitimate composing is the disclosure of law in concreto using statutory and conceptual approaches. The research results show that in this case BPOM can be held criminally liable because it essentially fulfills the elements of error due to negligence. Apart from that, if we examine the Criminal Code, the legal basis that can accommodate BPOM's actions is Article 205 of the Criminal Code because in this case BPOM was negligent in granting a distribution permit for the syrup medicine which resulted in MMR and resulted in the death of the child.